PANoptosis in intestinal epithelium: its significance in inflammatory bowel disease and a potential novel therapeutic target for natural products - Zhao, Chuanxiang; Lin, Shan (Frontiers in Immunology, 2025)
The intestinal epithelium, beyond its role in absorption and digestion, serves as a critical protective mechanical barrier that delineates the luminal contents and the gut microbiota from the lamina propria within resident mucosal immune cells to maintain intestinal homeostasis. The barrier is manifested as a contiguous monolayer of specialized intestinal epithelial cells (IEC), interconnected through tight junctions (TJs). The integrity of this epithelial barrier is of paramount. Consequently, excessive IEC death advances intestinal permeability and as a consequence thereof the translocation of bacteria into the lamina propria, subsequently triggering an inflammatory response, which underpins the clinical disease trajectory of inflammatory bowel disease (IBD). A burgeoning body of evidence illustrates a landscape where IEC undergoes several the model of programmed cell death (PCD) in the pathophysiology and pathogenesis of IBD. Apoptosis, necroptosis, and pyroptosis represent the principal modalities of PCD with intricate specific pathways and molecules. Ample evidence has revealed substantial mechanistic convergence and intricate crosstalk among these three aforementioned forms of cell death, expanding the conceptualization of PANoptosis orchestrated by the PNAoptosome complex. This review provides a concise overview of the molecular mechanisms of apoptosis, necroptosis, and pyroptosis. Furthermore, based on the crosstalk between three cell deaths in IEC, this review details the current knowledge regarding PANoptosis in IEC and its regulation by natural products. Our objective is to broaden the comprehension of innovative molecular mechanisms underlying the pathogenesis of IBD and to furnish a foundation for developing more natural drugs in the treatment of IBD, benefiting both clinical practitioners and research workers.